Selective Oxidation of Simple Aromatics Catalyzed by Nano-Biomimetic Metal Oxide Catalysts: A Mini Review - Wanna, Wondemagegn H.; Janmanchi, Damodar; Thiyagarajan, Natarajan; Ramu, Ravirala; Tsai, Yi-Fang; Yu, Steve S. F. (Frontiers in Chemistry, 2020)
The process of selective oxy-functionalization of hydrocarbons using peroxide, O3, H2O2, O2 and transition metals can be carried out by the reactive oxygen species such as hydroxyl/hydroperoxyl radical and/or metal oxygenated species generated in the catalytic reaction. Thus, a variety of mechanisms have been proposed for the selective catalytic oxidation of various hydrocarbons including light alkanes, olefins and simple aromatics by the biological metalloproteins and their biomimetics either in their homogeneous or heterogeneous platforms. Most studies involving these metalloproteins are Fe or Cu monooxygenases. The pathways carried out by these metalloenzymes in the oxidation of C-H bonds invoke either radical reaction mechanisms including Fenton’s chemistry and hydrogen atom transfer followed by radical rebound reaction mechanism or electrophilic oxygenation/O-atom transfer by metal-oxygen species. In this review, we discuss the metal oxide nano-catalysts obtained from metal salts/molecular precursors (M = Cu, Fe and V) that can easily form in situ through the oxidation of substrates using H2O2(aq) in CH3CN, and be facilely separated from the reaction mixtures as well as recycled for several times with comparable catalytic efficiency for the highly selective conversion from hydrocarbons including aromatics to oxygenates. The mechanistic insights revealed from the oxy-functionalization of simple aromatics mediated by the novel biomimetic metal oxide materials can pave the way towards developing facile, cost-effective and highly efficient nano-catalysts for the selective partial oxidation of simple aromatics.